2018
DOI: 10.1111/ina.12447
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of an electrostatic precipitator and a high-efficiency particulate air filter in building ventilation systems: Effects on cardiorespiratory health indicators in healthy adults

Abstract: High-efficiency particulate air (HEPA) filtration in combination with an electrostatic precipitator (ESP) can be a cost-effective approach to reducing indoor particulate exposure, but ESPs produce ozone. The health effect of combined ESP-HEPA filtration has not been examined. We conducted an intervention study in 89 volunteers. At baseline, the air-handling units of offices and residences for all subjects were comprised of coarse, ESP, and HEPA filtration. During the 5-week long intervention, the subjects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 52 publications
(68 reference statements)
1
54
0
Order By: Relevance
“…One disadvantage is that the filter may become a source of microbes if the retained microorganisms proliferate and enter back into the filtered air (Chuaybamroong et al, 2010). In addition, soiled HEPA filters are difficult to clean and expensive to replace (Day et al, 2018).…”
Section: Removal/filter Of Contaminated Airmentioning
confidence: 99%
“…One disadvantage is that the filter may become a source of microbes if the retained microorganisms proliferate and enter back into the filtered air (Chuaybamroong et al, 2010). In addition, soiled HEPA filters are difficult to clean and expensive to replace (Day et al, 2018).…”
Section: Removal/filter Of Contaminated Airmentioning
confidence: 99%
“…AHUs can be equipped with particle filters, e.g., minimum efficiency reporting value (MERV) or HEPA, with filtration efficiency dependent on particle size. HEPA filtration efficiency, f , is measured to be 99.994% at 50 nm, 99.98% at 0.1-0.2 mm, and >99.996% for particles >0.5 mm (Chuaybamroong et al 2010;Zhang et al 2014;Day et al 2018;Morono et al 2018). Because virus-laden particles are often expelled from the body in combination with proteins, salts, and water as droplets and aerosols (Dietz et al 2020), it is not yet clear whether aerosol transmission of SARS-CoV-2 is caused by suspended individual viral particles, of size $50À150 nm (Cascella et al 2020;Kim et al 2020), or larger respirable aerosols of size $1À5 mm (Singh and Kaur 2020; Wang and Du 2020).…”
Section: Physical Spaces: Laboratories and Officesmentioning
confidence: 99%
“…Exposure to these particles has been associated with enhanced aeroallergen sensitization, exacerbation of existing asthma, and the incidence of asthma among young and adolescent children . Studies have shown an increased risk of cardiovascular disease in individuals living near major roadways, implicating traffic air pollutants such as PM 2.5 , UFP, and BC as potential sources . Indoor exposure to microorganisms, microbial cell debris, allergens, and other particles in house dust has also become an area of interest in asthma and allergy research because of the potential adverse health effects …”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21] Studies have shown an increased risk of cardiovascular disease in individuals living near major roadways, implicating traffic air pollutants such as PM 2.5 , UFP, and BC as potential sources. [22][23][24][25][26][27] Indoor exposure to microorganisms, microbial cell debris, allergens, and other particles in house dust has also become an area of interest in asthma and allergy research because of the potential adverse health effects. 28,29 Portable air cleaners with high efficiency particulate air (HEPA) filtration and other high efficiency media have been evaluated for use in homes for the removal of smoke, dust, and fungal spores.…”
Section: Introductionmentioning
confidence: 99%